Oxidation combined with Maillard reaction induced free and protein-bound Nε-carboxymethyllysine and Nε-carboxyethyllysine formation during braised chicken processing - Zongshuai Zhu; Rui Fang; Ming Huang; Yunji Wei; Guanghong Zhou (Food Science and Human Wellness)
The objective of this work was to investigate the effects of oxidation and Maillard reaction on free and protein-bound Nε-carboxymethyllysine (CML) and Nε-carboxyethyllysine (CEL) formation during braised chicken processing. It was found that a positive correlation was observed between carbonyl, fat oxidation, Maillard reaction, CML and CEL (P < 0.05). The sulfhydryl groups could be used as potential indicators to evaluate the compounds’ interaction levels between Maillard reaction and protein oxidation. Frying promoted the formation of lysine (Lys), glyoxal (GO) and methylglyoxal (MGO) (P < 0.05); Boiling enhanced the formation of GO and MGO (P < 0.05) while inhibited the levels of Lys (P < 0.05); Sterilizing blocked the formation of MGO and Lys (P < 0.01) but improved GO levels (P < 0.05). Finally, a perspective was concluded that the Maillard reaction combined with oxidation is one of the main reasons for the formation of free and protein-bound CML and CEL during braised chicken processing.